2021
DOI: 10.24018/ejbmr.2021.6.6.1192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and Impact of Service Quality, Destination Image, on Customer Satisfaction and Revisit Intention to Syariah Destination in Madura, Indonesia

Abstract: Madura is one of the sharia tourist attractions in Indonesia, so many local and foreign tourists come to Madura Island to carry out sharia tours by visiting Islamic places such as mosques, tombs of the great Madurese clerics, and halal culinary places. In the conditions of the COVID-19 pandemic which has been going on for one year, government policy has closed these sharia tourist spots. However, since the number of Covid 19 cases, especially on Madura Island, has decreased significantly, the government has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
1
14
2
1
Order By: Relevance
“…However, the study of SQ, TS, and loyalty in the context of the tourism industry in a developing nation has yet to produce conclusive results. Contrary to Widayati et al's [35] assertions, the likelihood of a revisit or referral from a traveler with a positive BTI is independent of the quality of their trip. According to Li et al [56], PSQ did not influence TL's attitude towards the Cox's Bazar beach in Bangladesh, but it did influence their satisfaction.…”
Section: Service Quality Tourists' Satisfaction and Tourists' Loyaltycontrasting
confidence: 82%
See 1 more Smart Citation
“…However, the study of SQ, TS, and loyalty in the context of the tourism industry in a developing nation has yet to produce conclusive results. Contrary to Widayati et al's [35] assertions, the likelihood of a revisit or referral from a traveler with a positive BTI is independent of the quality of their trip. According to Li et al [56], PSQ did not influence TL's attitude towards the Cox's Bazar beach in Bangladesh, but it did influence their satisfaction.…”
Section: Service Quality Tourists' Satisfaction and Tourists' Loyaltycontrasting
confidence: 82%
“…Similarly, Wantara [34] specifies that tourists form a more sophisticated image of an area due to their interactions and activities while on vacation. Returning visitors have a more positive view of a destination than first-time visitors [35]. This process of changing a destination's image is continual, and an image will evolve due to events that occur throughout the visit [36].…”
Section: Destination Imagementioning
confidence: 99%
“…Furthermore, Ordanini & Parasuraman (2011) found that both innovation radicalness and innovation volume positively affect service satisfaction. Having a new service concept, new customer interaction, new value system/business partners, new revenue model, new organizational delivery system, and new technological delivery system leads to greater service satisfaction (Ofosu-Boateng & Acquaye, 2020;Wantara & Irawati, 2021). Thus, this study hypothesizes: H8: Service innovation has a positive effect on service satisfaction.…”
Section: G Hypothesis Developmentmentioning
confidence: 95%
“…This approach has very broad service attributes and is very practical for use in various service companies. This instrument was created to measure the quality of services such as hotels (Rao & Sahu), hospitals (Agbonifoh & Agbonifoh, 2015), telephone companies, transport companies, insurance companies, banks (Parasuraman et al, 1991) and tourism (Wantara, & Irawati, 2021). According to Bello & Majebi (2018), the SERVQUAL model can be employed to measure service quality in all the service based industries.…”
Section: Service Qualitymentioning
confidence: 99%